A VALIDATED HPTLC METHOD FOR SIMULTANEOUS QUANTIFICATION OF NEBIVOLOL AND HYDROCHLOROTHIAZIDE IN BULK AND TABLET FORMULATION (International Journal of Pharmaceutical Sciences and Drug Research, 2011)
A HPTLC method for the estimation of Nebivolol (NBV) and Hydrochlorothiazide (HCTZ) has been developed. It employs aluminum backed silica gel 60 F254 TLC plates, (20 cm × 10 cm, layer thickness 0.2 mm) pre-washed with methanol and mobile phase comprising of 1,4-dioxane: toluene: triethylamine (5:3:0.1 v/v). The developing solvent was run up to 80 mm in Camag chamber previously saturated with 10.0 ml of solvent mixture for 30 min. Densitometric scanning was then performed with Camag TLC Scanner-3 equipped with winCATS (version 1.3.0) at λ max 281 nm. The Rf values were found to be 0.75 and 0.43 for Nebivolol and Hydrochlorothiazide respectively. The limit of detection and limit of quantitation were found to be 43ng/spot & 130ng/spot for Nebivolol and 25ng/spot & 76ng/spot for Hydrochlorothiazide respectively. The % RSD of intra-day variation and inter day variation were 0.54 and 0.41 respectively for NBV and 0.46 and 0.39 for HCTZ respectively. The proposed method can also be used for routine quality control to accurately determine Nebivolol and Hydrochlorothiazide in bulk and tablet dosage form.